THE CHALLENGES FACED BY ENGLISH TEACHERS IN TEACHING LISTENING SKILL AND ATTITUDE AT JUNIOR HIGH SCHOOL BASED ON CURRICULUM 2013 - Aryuliva Adnan (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
Curriculum 2013 has been socialized since the beginning of 2013 and it has been implemented since 2013/2014 academic year for the first year students of elementary, secondary and senior high school. One of the crucial factors stated in curriculum 2013 is attitude competence besides the other competences knowledge and skill. Including attitude in curriculum as the core competence will become a challenge for the English teachers, because the three core competences have to be integrated with language skills. Besides the other challenge is the in availability of listening materials (cassette or CD) for teaching listening skill in secondary level. Keywords: attitude competence, listening skill.